Ras Homolog Family Member A Regulates Interleukin-6 Expression in Streptozotocin-Pretreated Mice with Relevance to Alzheimer’s Disease-Related Inflammation - Abdulrahman, Kanyaw; Hwaiz , Rundk (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: Alzheimer’s disease (AD) is a slowly worsening brain disorder linked to ongoing inflammation, with interleukin-6 (IL-6) playing a significant role in its progression. Ras Homolog Family Member A (RhoA) regulates inflammatory signaling and may influence IL-6 expression in AD. This research aimed to investigate the impact of RhoA inhibition on IL-6 expression and neuropathology in a streptozotocin (STZ)-induced AD mouse model. Methods: A total of 15 male Swiss albino mice, aged 8–9 weeks and weighing 25–30 g, were randomly assigned into three groups (n = 5 per group): Control (control), STZ-pretreated (diabetes-associated cognitive impairment like Alzheimer’s diseasemodel), and Y-27632+STZ (RhoA inhibitor-treated). The treatment group received 5 mg/kg Y-27632 before STZ administration. ELISA measured IL-6, amyloid beta 42 (Aβ42), and tau levels in brain and serum. Histopathological analysis assessed neuroinflammation and neuronal damage. Results: STZ significantly increased Aβ42, tau, and IL-6 levels (P <0.05). Y-27632 treatment reduced these markers, indicating neuroprotection. Histological analysis revealed severe neuroinflammation and neuronal damage in the STZ group, while Y-27632 reduced inflammatory cell infiltration and brain injury scores (P <0.05). Conclusion: RhoA inhibition attenuates IL-6-mediated neuroinflammation, decreases tau and amyloid plaque pathology, and mitigates neurodegeneration in AD. Targeting RhoA may offer a promising therapeutic approach for AD management.